Helicobacter pylori sabA, hopQ and hom genotypes as potential genetic biomarkers for gastric mucosal inflammation - Hunowu, Ramdan; Fauzia, Kartika A.; Alfaray, Ricky I.; Dewi, Selva R.; Juniastuti, Juniastuti; Yamaoka, Yoshio; Miftahussurur, Muhammad (Narra J, 2025)
Helicobacter pylori infection drives heterogeneous gastric pathologies, yet genotype-phenotype correlations in diverse populations remain underexplored. The aim of this cross-sectional study was to investigate the associations between H. pylori virulence genotypes (sabA, hopQ, hom family) and histopathological severity in gastric mucosa among 113 Indonesian dyspepsia patients (mean age: 49.6 years; male predominance: 64.6%). Whole-genome sequencing characterized virulence genotypes, while histopathological grading system using the Updated Sydney System assessed inflammation, atrophy, and bacterial density in the antral and corporal gastric regions. Phylogenetic analysis elucidated strain relatedness. Key genotype frequencies included sabA "on" (40.6%, 43/106), hopQ type I (53.7%, 43/80), and homCL (82.4%, 75/91). Statistical analysis revealed sabA "on" status significantly associated with elevated antral bacterial density (odds ratio (OR) 2.70 and 95% confidence interval (95%CI) 1.10–6.60, p=0.027). The homC variants (homCL/homCS) demonstrated robust associations with chronic inflammation severity (OR: 3.04; 95%CI: 0.99–9.36, p=0.046) and atrophy progression (OR: 4.78; 95%CI: 1.00–22.86, p=0.035), in contrast to the hopQ genotype, which showed no histopathological association. These findings indicated that sabA and homC as critical determinants of gastric microenvironment modulation, potentially through sabA-mediated colonization efficiency and homCL-babA synergistic interactions. While histological profiles predominantly indicated mild atrophy, widespread severe chronic inflammation signals latent progression risks.